Applying Spatial Augmented Reality to Anti-Smoking Message: Focusing on Spatial Presence, Negative Emotions, and Threat Appraisal. Issue 9 (28th May 2019) - Lee, Jiyoung; Jung, Soyoung; Kim, Ji Won; Biocca, Frank
ABSTRACT: As smoking has emerged as a health-risk behavior, communication scholars and practitioners have put many efforts into finding out ways to achieve smoking cessation. In this research, participants ( N = 57) were randomly assigned to a spatial augmented reality (SAR) condition (3D projection mapping) and 2D flat screen to be exposed to an anti-smoking message. This research provides insightful evidence that the effects of SAR on people's behavioral intention to spread anti-smoking messages online could be explained by spatial presence and negative emotions. Implications for research on the potential of SAR in terms of emotions and online viral behavioral intentions are discussed.